The Urgency of Personal Data Protection for UMKM Actors as Users of OSS-RBA - Ajeng Pramesthy H.K (Private Law Department, Faculty of Law, University of Jember, Indonesia, 2023)
The development of technology in the economic world is rapidly advancing into the era of hybrid work. Most economic activities rely on technology to solve their problems. One concrete example is the OSS-RBA program for UMKM actors. OSS-RBA (Online Single Submission Risk Based Approach) is a form of technological advancement in risk-based business licensing supervision, differentiated by the scale of business activities. One of the functions of OSS-RBA is to store personal data with the expectation of keeping user data confidential and secure. The users of OSS-RBA are UMKM actors who engage in productive economic activities that meet the criteria of Micro, Small, and Medium Enterprises. The existence of UMKM cannot be eliminated or avoided from society because it provides benefits such as absorbing a large-scale workforce, which can reduce unemployment rates and create production creativity, thereby increasing people's purchasing power. Therefore, the development of UMKM is very strategic in driving the national economy. In connection with this, the protection of personal data becomes an essential aspect to be implemented in society, especially for UMKM actors as users of OSS-RBA. Personal data protection for OSS-RBA users, namely UMKM actors, becomes an urgency to be applied. The trust of UMKM actors in the OSS-RBA program will be relatively high if their personal data protection is guaranteed. Thus, by standardizing the protection of personal data related to the use of OSS-RBA for UMKM actors, the success of their business will have a broad impact on the Indonesian economy.